Hubungan Promosi Terhadap Kepuasan Konsumen Shopee Pada Karyawan Di PT. Morich Indo Fashion 2 Karangjati Kabupaten Semarang - Retno Djohar Juliani; Dewi Fatmasari; Liana Dewi Saraswati (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to determine the relationship between promotions and Shopee consumer satisfaction among employees of PT Morich Indo Fashion 2 Karangjati, Semarang Regency. This research includes quantitative descriptive research. The research population was employees of PT Morich Indo Fashion 2, totaling 2,000 people. The sample calculation uses the Issac and Michael formula with a sample size of 95 respondents. The sample was selected or purposive random sampling, namely employees of PT Morich Indo Fashion 2 Karangjati who used Shopee. The measurement technique uses a 5-level Likert scale. For promotion, it uses a scale of very good, good, quite good, not good and very not good. Meanwhile, consumer satisfaction uses a scale of very satisfied, satisfied, quite satisfied, dissatisfied and very dissatisfied. Data sources include primary data and secondary data. The data collection technique uses a questionnaire. The data is presented in the form of a frequency distribution table and analyzed using cross tabulation. Based on the results of research on respondents (employees) of PT Morich Indo Fashion, Shopee promotions were very good and consumers were satisfied, namely 4 people (4%). A total of 82 people (86%) said the promotion was good and consumers were satisfied. A total of 9 people (10%) stated that Shopee promotions were quite good and consumers were satisfied. So it can be concluded that the better the promotion, the more satisfied the consumer will be and conversely, the less good the Shopee promotion, the less satisfied the consumer will be. The suggestions that can be given for promotions are that Shopee needs to pay attention to the content of advertising messages so that it is easier for consumers to understand, the seller's response must be good and apologize when consumers make claims, promotions on Shoppe must be made more attractive compared to other e-commerce. Shoppe must improve its good name as an e-commerce by providing publicity regarding the cheapest guarantee claims and free shipping guarantees. Meanwhile, suggestions for consumer satisfaction that shops or sellers on Shopee must maintain and improve the quality of the products sold so that they meet consumer desires, are always carried out before the goods are sent. quality control so that the goods received are not recorded/rejected. The product display in the application should use product photos that correspond to reality. When consumers make a purchase, it is best to pack it on that day and hand it over directly to the expedition so that it can be sent to the consumer immediately.